FORMATION OF EMOTIONAL CULTURE OF STUDENTS (Pedagogy of Higher and Secondary Education, 2022)
The article deals with the investigations of basic notions of the theme under investigation. The structure and the content of the emotional culture of pupils are analyzed and the basic ways of its forming are shown.
Keywords: pupils; emotion; culture; emotional culture